Application of the house of risk matrix methodology for supply chain management risk mitigation - Ningsih, Gita Wahyu; Ernawati, Dira; Nugraha, Isna (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
For a company, efficient operations hinge on a robust supply chain system. Consequently, it is crucial to manage a well-structured supply chain system effectively. This research examines a manufacturing firm that specializes in producing heavy equipment for industrial applications. The firm adopts a make-to-order (MTO) production strategy, requiring it to order raw materials from suppliers in advance. However, this approach poses multiple risks, including delays or mistakes in raw material deliveries, which directly lead to setbacks in production. In response to these issues, this study seeks to pinpoint potential risks and formulate risk mitigation strategies using the House of Risk (HOR) method. The HOR method is a sophisticated tool tailored for risk mitigation analysis. Through this research, 21 risk events and 15 risk agents were identified, leading to the development of 25 prioritized mitigation strategies to tackle the risks in the company’s supply chain system. These strategies are anticipated to assist the company in reducing supply chain risks, thereby promoting more seamless and effective operational performance.